Pengaruh Hak Asasi Manusia Yaitu Hak Memiliki Keturunan dan Berkeluarga dengan Hukuman Kebiri Kimia Bagi Pelaku Kekerasan Seksual - Saffana Ayu Azzahra (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study critically examines the intersection between chemical castration as a criminal sanction and the protection of human rights, particularly the right to form a family and to procreate, within the Indonesian legal system. Employing a normative-doctrinal legal research method, the analysis integrates statutory, conceptual, and limited comparative approaches to assess the coherence of Law Number 17 of 2016 with national and international human rights standards. The findings reveal that chemical castration raises substantial normative tensions, particularly in relation to bodily integrity, reproductive rights, and non-derogable rights protected under constitutional and international frameworks. Furthermore, the policy demonstrates limited effectiveness when evaluated through deterrence theory, as it fails to satisfy the elements of certainty, severity, and celerity, while lacking empirical support as a reliable crime prevention mechanism. Comparative analysis indicates that more balanced approaches—combining voluntary measures, psychological rehabilitation, and medical oversight—offer greater legal and practical legitimacy. The study concludes that the current framework requires comprehensive reform through implementing regulations, integrative rehabilitation models, and rights-based safeguards to ensure proportionality, legal certainty, and alignment with contemporary criminal justice principles.